Download presentation

Presentation is loading. Please wait.

Published byJoshua Edwards Modified over 8 years ago

1
Solving Equations

2
-132 = 4x – 5(6x – 10) -132 = 4x – 30x + 50 -132 = -26x + 50 -182 = -26x 7 = x

3
-6x + 2(-4x – 17) = 78 -6x – 8x – 34 = 78 -14x – 34 = 78 -14x = 112 x = -8

4
-98 = -7x – 4(2x – 13) -98 = -7x – 8x + 52 -98 = -15x + 52 -150 = -15x 10 = x

5
5x – 2(-2x – 17) = 124 5x + 4x + 34 = 124 9x + 34 = 124 9x = 90 x = 10

6
26 = -7x – 4(2x – 13) 26 = -7x -8x + 52 26 = -15x + 52 -26 = -15x 1.73 = x

7
4x + 4(-6x – 6) = -144 4x – 24x – 24 = -144 -20x – 24 = -144 -20x = -120 x = 6

8
137 = -5x + 4(5x +8) 137 = -5x + 20x + 32 137 = 15x + 32 105 = 15x 7 = x

9
186 = 6x – 4(7x – 8) 186 = 6x – 28x + 32 186 = -22x + 32 154 = - 22x -7 = x

Similar presentations

© 2023 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google